2012
DOI: 10.1115/1.4006423
|View full text |Cite
|
Sign up to set email alerts
|

Natural Frequency Shift in a Centrifugal Compressor Impeller for High-Density Gas Applications

Abstract: In designing an impeller for centrifugal compressors, it is important to predict the natural frequencies accurately in order to avoid resonance caused by pressure fluctuations due to rotor-stator interaction. However, the natural frequencies of an impeller change under high-density fluid conditions. The natural frequencies of pump impellers are lower in water than in air because of the added mass effect of water, and in high-pressure compressors the mass density of the discharge gas can be about one-third that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Horta-Rangel et al (2008) analysed the shift in natural frequencies of structures and proposed the best method to repair damaged bridges. Magara et al (2013) proposed a theoretical method to find the natural frequency for centrifugal pumps and implemented experimental methods to verify results. Their results indicated that for high-density centrifugal compressors, some natural frequencies of an impeller increased with a high-density gas.…”
Section: Introductionmentioning
confidence: 99%
“…Horta-Rangel et al (2008) analysed the shift in natural frequencies of structures and proposed the best method to repair damaged bridges. Magara et al (2013) proposed a theoretical method to find the natural frequency for centrifugal pumps and implemented experimental methods to verify results. Their results indicated that for high-density centrifugal compressors, some natural frequencies of an impeller increased with a high-density gas.…”
Section: Introductionmentioning
confidence: 99%
“…Because changes in the frequency of oscillation due to the surrounding fluid are usually generated entirely by the added mass [24,25], observing the oscillatory behavior of a known mass has allowed the behavior of this added mass occurrence to be explored in many studies [26][27][28][29]. Hamilton presented a vibrational technique for determining the added mass of submerged objects during deployment of subsurface moorings [26].…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Hsieh measured added mass and added mass moment of inertia of several floating bodies under heave and pitch motions as functions of frequency [27]. Magara et al characterized the added mass of an impeller rotating in dense gas by analyzing the shift in its natural frequency [28]. Zhao et al developed a method to measure fluid density using a vibrating micro-cantilever [29].…”
Section: Introductionmentioning
confidence: 99%